Trunk appearance perception scale for physicians (TAPS-Phy) - a valid and reliable tool to rate trunk deformity in idiopathic scoliosis. Issue 1 (December 2016) - Matamalas, Antonia; D'Agata, Elisabetta; Sanchez-Raya, Judith; Bago, Juan
Abstract Background Evaluation of trunk deformity by physicians in patients with idiopathic scoliosis (IS) has been considered an important part of clinical practice. Different methods to quantify the severity of trunk deformity by external observation have been reported. A valid tool to evaluate patients' perception of trunk deformity, the Trunk Appearance Perception Scale (TAPS), is hereby validated for use by physicians (TAPS-Phy). Methods Cross-sectional study of patients with non-surgically treated IS. Patients were prospectively recruited. On the day of the visit, a posterior-anterior radiograph in standard position and clinical photographs in three different views (anterior, posterior and forward bending position) were obtained. Patients also completed a TAPS questionnaire (TAPS-Pat). Three different observers scored the TAPS questionnaire (TAPS-Phy), based on the digital photographs previously obtained, twice a week. The angle of trunk inclination (ATRI) was also measured on digital photographs. Inter and intra-rater reliability was calculated through weighted kappa coefficient. External validity was tested by the Spearman correlation coefficient between the TAPS-Phy score and the scoliosis magnitude determined using the magnitude of the largest curve (MLC), ATRI, and TAPS-Pat. Results Fifty two patients (46 women; mean age 16.6 years) were included. The average curve magnitude of the major curve was 44°. Mean scores of TAPS-Phy for the three evaluators ranged from 3.4 to 3.5. No differences between the three means were found. TAPS-Phy showed good internal consistency (Cronbach's alpha coefficient 0.84). Inter-observer reliability ranged from slight to substantial (0.14 to 0.63); intra-observer reliability ranged from 0.35 to 0.99. Correlation between TAPS-Phy and ATRI (r  = −0.54 to −0.75), MLC (r  = −0.47 to −0.6) and TAPS-Pat (r  = 0.29 to 0.34) were statistically significant (p  < 0.01). Conclusions TAPS-Phy is a valid and reliable scale to rate a physician's impression of the severity of the deformity in patients with idiopathic scoliosis and can be useful in routine clinical records.